Ergonomie spatiale pour territoires résilienciels : approches et perspectives - Eliane Propeck-Zimmermann; Thierry Saint-Gérand; Hélène Haniotou; Sophie Liziard; Mohand Medjkane (VertigO)
The use of spatial ergonomics in resilience issues is based on the hypothesis that the ability of a territory to recover its basic functions after a disaster depends on its overall performance level already present during normal times to make available its resources (in the broad sense: services, activities, supplies, communication, etc.). It is thus necessary to model the system of spatial, functional and cost / effort constraints, conditioning, at different spatial and temporal scales, access to the resources of a territory, by its population and its decision-makers (Institutions, Companies), in ordinary situation and in a degraded situation. We present here a first exploration on the capacity of the relation "spatial ergonomics / territorial resilience" to produce diagnostic tools to help develop a resilient management. The methodological approach to analyzing and mapping a degree of spatial ergonomics within a territory will be presented through an experimental example on the Strasbourg agglomeration. The aim of the whole process is to build a synthesis that can help define an innovative scheme for resilient organization and operation issues.